2017
DOI: 10.18632/oncotarget.20910
|View full text |Cite
|
Sign up to set email alerts
|

UCHL1 expression and localization on testicular development and spermatogenesis of Chinese giant salamanders

Abstract: Ubiquitin carboxyl-terminal hydrolase L1 (UCHL1), which is extensively expressed in vertebrates, is a deubiquitinating enzymes that inhibits the degradation of proteins by reversing ubiquitination modification. Herein, a 1087-bp sequence encoding UCHL1 was identified from the Chinese giant salamander (CGS; Andrias davidianus). The coding sequences (CDS) of UCHL1 encoded a putative poly peptide of 222 amino acids. The CGS UCHL1 isoforms were more related to their human and mouse counterparts. The phylogenic tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Notably, the UCHL1 gene is expressed in rodent spermatogonia and Sertoli cells, whereas in other mammals, including humans, non-primates, and domestic animals, it is expressed only in spermatocytes and the spermatogonia of seminiferous tubules [39]. UCHL1 is considered the most appropriate marker of spermatogonia and meiosis in male germ cells, consistent with the result of the present study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Notably, the UCHL1 gene is expressed in rodent spermatogonia and Sertoli cells, whereas in other mammals, including humans, non-primates, and domestic animals, it is expressed only in spermatocytes and the spermatogonia of seminiferous tubules [39]. UCHL1 is considered the most appropriate marker of spermatogonia and meiosis in male germ cells, consistent with the result of the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Five potential genes, including UCHL1, DDX4, SOHLH1, KITLG, and PCNA, were identified, displaying different levels of their expressions during the process of spermatogenesis. For example, UCHL1 (PGP9.5), a deubiquitinating enzyme, inhibits protein degradation by reversing ubiquitin modifications [39]. Differences in the localization of UCHL1 play important roles in regulating cell proliferation and differentiation through the post-translational ubiquitination of proteins [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We utilized two antibodies; one of them is for a synaptic and neuron-specific protein Homer1, which is a scaffold protein associated with the plasma membrane, and the other one is for a pan-neuronal marker PGP9.5, also known as UCHL1, which mainly localizes in the cytosol. 32,33) The anti-Homer1 and PGP9.5 antibodies reacted with neuronal cell bodies in the trigeminal ganglia and did not show any change in the staining pattern by ethanol administration (Fig. 5A-D).…”
Section: Resultsmentioning
confidence: 93%
“…Previous studies have shown that the UCH family plays different roles in the progression of different tumors[40]. Ubiquitin carboxyl terminal esterase L1, a family member of UCHs, is not only overexpressed in neural tissue[41] but is also used as a marker of nerve fibers to study PNI[42].…”
Section: Discussionmentioning
confidence: 99%